METHODS OF EVALUATION OF ANTIBIOTIC PRESCRIPTION IN DENTISTRY - Ioana Maria Hunea; Aurelia Cretu; Cristina Mihaela Ghiciuc; Daniela Anistoroaiei; Georgeta Zegan (Romanian Dental Association for Education, 2019)
Dentists are important antibiotic prescribers, therefore their therapeutic decisions should contribute to the rational use of antibiotics. Our study aim was to analyse the modalities to evaluate the prescription patterns among dental practitioners. Material and methods. Relevant studies from MEDLINE/PubMed database, published in English, in the interval 1980-2019, evaluating the patterns of prescription of antibiotics in dentistry were selected. We excluded the studies presenting only data about the knowledge regarding antibiotics in dental practice. We recorded the type of study, the modality of collection of data, the response rate, and the characteristics about the prescription behaviour. Results. The most frequently used modality for the evaluation of antibiotic prescribing patterns in dentists was realized through cross-sectional or longitudinal studies. Another modality to evaluate antibiotic prescribing patterns in dentistry was the analysis of prescriptions from dental practitioners. Conclusions. The study demonstrates need to for more research studies and for educational initiatives to prevent inappropriate recommendation of antibiotics in dentistry.